2012
DOI: 10.1017/s0266462312000244
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Alemtuzumab for T-Cell Prolymphocytic Leukemia

Abstract: Alemtuzumab appears more likely to be cost-effective if used earlier in the course of T-PLL and where it replaces the use of multiple alternative therapies. However, cost-effectiveness is highly uncertain and future research is clearly justified. Nevertheless, our analysis demonstrates the feasibility of considering the cost-effectiveness of an agent despite the presence of significant uncertainty to provide appropriate assessment information to policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Utility values can range from 1.00 (perfect health) to 0.00 (death) in the model. Published disease-specific utilities for patients with APL were not availabletherefore it was assumed that chronic lymphocytic leukemia (CLL) utility estimates from Woods 28 and Ferguson 29 were applicable to patients with APL, an approach that has been used in previous leukemia research 30 . To address a limitation of using CLL utilities (i.e., that CLL patients are typically older and have worse outcomes than APL patients), age-adjusted utilities were calculated for the model.…”
Section: Methodsmentioning
confidence: 99%
“…Utility values can range from 1.00 (perfect health) to 0.00 (death) in the model. Published disease-specific utilities for patients with APL were not availabletherefore it was assumed that chronic lymphocytic leukemia (CLL) utility estimates from Woods 28 and Ferguson 29 were applicable to patients with APL, an approach that has been used in previous leukemia research 30 . To address a limitation of using CLL utilities (i.e., that CLL patients are typically older and have worse outcomes than APL patients), age-adjusted utilities were calculated for the model.…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al compared alemtuzumab with conventional chemotherapy in people with T-cell prolymphocytic leukemia and reported depending on different assumptions incremental QALYs ranging between 0.16 and 0.24 [60].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…Eight studies examining the costs or cost-effectiveness of alemtuzumab, ipilimumab, sipuleucel-T, or ofatumumab, were included in the final analyses. [25][26][27][28][29][30][31][32] Table 2 summarizes findings of review articles identified from the phase I search regarding the cost-effectiveness of therapeutic cancer vaccines and immunotherapy in the current literature. As shown, rituximab combined with chemotherapy was considered to be costeffective for non-Hodgkin's lymphoma (NHL) when compared to chemotherapy alone.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Four cost-effectiveness studies were identified from the Phase II search, covering alemtuzumab (for T-cell prolymphocytic leukemia, T-PLL), ipilimumab (for previously treated advanced melanoma), sipuleucel-T (CRPC), and ofatumumab (for CLL) (table 4). [29][30][31][32] Lu et al reported that while alemtuzumab (vs. chemotherapy) was likely to be cost-effective for T-PLL, especially if used earlier in the course of treatment, the cost-effectiveness of alemtuzumab is highly uncertain (ICER $42,710 » $119,701/ QALY among four scenarios). 29 Barzey et al reported that the probability that ipilimumab was cost-effective relative to BSC at willingness-to-pay (WTP) of $146,000 USD/QALY was 95% for patients with previously treated advanced melanoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation